HUKUM ISLAM PADA MASA IMAM-IMAM MUJTAHID (101 H – 350 H / 750 M – 961 M) - Darmawati Darmawati (Sulesana: Jurnal Wawasan Keislaman, 2012)
Knowledge has developed rapidly during the reign of Abbasids, it is because of government policy at that time a love of knowledge. Both the knowledge of tafsir, hadith, the knowledge of kalam, as well as jurisprudence. Another cause of the development of science in the Abbasid period because it has been given the freedom to think and develop science in their respective fields. By him that Islamic law has developed rapidly as any other science. At this time some priests born mujtahid. Imam Abu Hanifah, Imam Malik, Imam Shafi'i and Imam Ahmad ibn Hanbal.